2007
DOI: 10.1117/12.754190
|View full text |Cite
|
Sign up to set email alerts
|

A novel microstructured fiber optic sensor for small deformations

Abstract: This paper will detail novel enabling fiber optic sensors based on the use of the photonic structures embedded in the core of the fiber. We will start by briefly reviewing fiber optics used as sensors for mechanical deformations, and introducing photonic crystals characteristics. Afterwards we will show that embedding photonic crystal structures into standard monomode fiber optics allows for highly sensitive detection of mechanical deformations. Finally, we will show simulation results using EMExporer which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Our simulations have shown that measuring the output phase variations (of the electromagnetic components) could provide very precise information about deformations. The triangular-lattice PC sensor improves the sensitivity by 22% (when compared to the rectangular-lattice PC sensor presented previously [10][11][12]). …”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Our simulations have shown that measuring the output phase variations (of the electromagnetic components) could provide very precise information about deformations. The triangular-lattice PC sensor improves the sensitivity by 22% (when compared to the rectangular-lattice PC sensor presented previously [10][11][12]). …”
Section: Discussionmentioning
confidence: 83%
“…In our previous work [10][11][12] we have determined that a rectangular-lattice PC structure achieves a sensitivity S rectangular = 12.51pm/º for the same loading condition). This means that the triangular-based sensor is 22% better (more sensitive) than the rectangularbased one (as 9.75pm/° / 12.51pm/° 0.78).…”
Section: Simulations Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In several recent papers [10][11][12] we have investigated and reported on embedding a rectangular-lattice PC structure into the core of standard monomode FOs. We have shown that such sensors allow for highly sensitive detection of mechanical deformations using the classical sensing principle (illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%